PERAN GURU BIMBINGAN DAN KONSELING DALAM PENDIDIKAN INKLUSI - Abdul Hadi; Palasara Palasara Brahmani Laras (Jurnal Selaras : Kajian Bimbingan dan Konseling serta Psikologi Pendidikan, 2021)
ABSTRACT Dynamics The development of national education leads to the model of inclusive education. Schools as educational institutions that accept children with special needs and are able to facilitate education services in accordance with the physical and psychological aspects of students. The role of Teacher Guidance and Counseling is carried out to carry out services in inclusive education, including identifying sources that support inclusive education, compiling instruments for measuring the success of implementing inclusive education, making changes or improving programs based on the results of assessment of inclusive education. in order to achieve development and optimism in the education process. Keyword: Role of Teacher Guidance and Counseling, Inclusive Education